2020
DOI: 10.3389/fimmu.2020.00261
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cells Enriched for a Dendritic Cell Population From People Living With HIV Have Altered Gene Expression Not Restored by Antiretroviral Therapy

Abstract: Antiretroviral therapy (ART) for human immunodeficiency virus (HIV) infections has been designed to optimize CD4 T-cell survival and limit HIV replication. Cell types other than CD4 T cells such as monocytes/macrophage, dendritic cells, and granulocytes (collectively known as myeloid cells), are generally not considered in the development of ART protocols. Myeloid dendritic cells (mDCs) are the most potent inducers of CD4 T-cell activation and central to the regulation of immune responses. mDCs in the blood ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Studies in vitro with human DCs have demonstrated that some of these cells are susceptible to the infection with HIV, such as Langerhans cells, cDCs, and pDCs (253,254). Interestedly, cDCs from HIV patients have shown low levels in the blood, and their function is compromised (255). When HIV infects DCs, it can travel within the cell until it locates memory CD4 + T cells into the lymphoid tissue, spreading the infection in this way (256,257).…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vitro with human DCs have demonstrated that some of these cells are susceptible to the infection with HIV, such as Langerhans cells, cDCs, and pDCs (253,254). Interestedly, cDCs from HIV patients have shown low levels in the blood, and their function is compromised (255). When HIV infects DCs, it can travel within the cell until it locates memory CD4 + T cells into the lymphoid tissue, spreading the infection in this way (256,257).…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Upon the HIV-infection of cDCs, the anti-viral pathways within these cells are changed, and as a result, it promotes the viral spreading. However, the use of antiretroviral therapies (ART) can return completely the functionality of the pathways IL-1 and type I IFN (255,259).…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…Although AOAH was intially found in neutrophils (9), cellular levels of AOAH are often lower in circulating and exudate neutrophils than in monocytes/macrophages, hepatic Kupffer cells (56), immature dendritic cells (57,58), and NK cells. AOAH expression has also been found in mucosal ILC1 cells, which are closely related to NK cells but lack granulysin and perforin and have a genomic 'superenhancer' region that includes part of the AOAH gene (59).…”
Section: Cellular Sources Of Aoahmentioning
confidence: 99%
“…Some of this is attributed to exposures such as tobacco smoking (7,8) and ART-related toxicity (9), but predictors of clinical outcome in this context also include circulating markers of inflammation such as pro-inflammatory cytokines (IL6), acute phase proteins (CRP, fibrinogen) and markers of leukocyte activation (soluble CD14 and CD163), suggesting persistent immune dysregulation in PLHIV despite effective ART (10,11). Enrichment of pro-inflammatory states has also been reflected in transcriptional studies of blood monocytes (12), myeloid dendritic cells (13) and CD4 T cells (14) from ART-treated PLHIV. The immunological pathways that underpin these observations are not fully understood.…”
Section: Introductionmentioning
confidence: 99%